Assessing equilibrium clear water scour around single cylindrical piers - Lança, Rui (2014)
The objective of this research is to investigate the pertinence of existing approaches to assess the onset of the equilibrium phase of scour at single cylindrical piers in experimental studies. The results of five long-lasting experiments are reported. The discussion has profusely shown that common methods used to decide on whether a given scour experiment has reached the equilibrium phase may be erroneous. It has also shown that known predictors of time to equilibrium may imply significantly wrong predictions of equilibrium depth. Finally, it seems that, typically, 7 days-long scour depth records adjusted though a 6-parameters polynomial function and extrapolated to infinite time render robust vales of the equilibrium scour depth at single cylindrical piers.